UPAYA DETEKSI DINI DAN PENCEGAHAN PENULARAN TUBERKULOSIS MELALUI PENDEKATAN DOOR TO DOOR DAN EDUKASI MASYARAKAT DI DESA KASANG KUMPEH - Kiki Andrean; Hendra Dhermawan Sitanggang; Dwi Noerjoedianto; Inggrit Vanesa; Tsaabitah Zakhirah; Puji Rahmiyati Awaliyah; Hasmil Arifqi; Rosiana Putri; Erika Vernanda Br Lbn Toruan; Naila Nur Ramadani; Yolanda Margarettha Silaban; Indira Harti; Ahmad Thohir Hidaya (Jurnal Riset Multidisiplin Edukasi, 2025)
This report examines efforts for early detection and prevention of tuberculosis (TB) transmission in Kasang Kumpeh Village, Kumpeh Ulu District, Muaro Jambi Regency, through a door-to-door approach and community education. The program aims to raise public awareness of the importance of TB screening, early detection, and adherence to treatment. Screening activities were conducted in three high-risk RTs, with results showing that most of the community had low knowledge about TB. Interventions were carried out by providing household-based education and engaging the community in prevention efforts through the SIMPATIK (Community Synergy for TB and Health Awareness) program. Additionally, tuberculosis preventive therapy (TPT) was given to high-risk families. Evaluation results showed significant improvement in the community's knowledge about TB after the intervention, and successful identification of potential cases of TB transmission.